Holistic System Design Evaluation Through Expanded MATE - Yeager, Matthew P.; Holzer, Thomas H.; Willy, Christopher J.; Sarkani, Shahryar (IEEE engineering management review, 2020)
According to Buede and Miller, not applying a holistic simulation and modeling approach to early design evaluation practices and trade studies results in greater developmental costs, time to market, and unforeseeable system-level design consequences. Completed research is presented for an innovative methodology that enhances the capacity of conventional design evaluations by integrating new types of simulations consistently into the existing Multi-attribute Tradespace Exploration (MATE) design evaluation architecture. This enhancement is particularly important for any envisioned software-intensive system that introduces greater system complexity. According to Ross et al., MATE was originally developed to guide engineering design and initial product selection by exploring candidate designs to deliver utility-based solutions. Unfortunately, the MATE methodology does not support software design evaluation and integration into complex systems. The results presented validate MATE improvements that are scalable and extensible to any software-based system of varying complexity and application. The subject research provides proof of this concept by focusing on sensor systems as an initial practical demonstration due to their rapidly expanding commercial use and Internet of Things (IoT) applications. Project engineers and especially software developers in any product field will benefit from this design method by leveraging its holistic evaluation of software and hardware system design performance for more efficient product design identification and implementation.